The political economy of refugee migration and foreign aid - Czaika, Mathias (Basingstoke, UK ; New York : Palgrave Macmillan, 2009)
This book inquires the determinants of forced migration, describes the distribution of burdens from forced migration across countries, and analyzes the strategic interaction of national refugee policies to control refugee flows. Emphasis is put on the role of asymmetries between countries with respect to their preferences regarding immigrants, the costs incurred by immigrants, their stage of development and especially their geographical position as neighboring first asylum country or Western asylum country. Special attention is given to one policy instrument to control refugee migration flows, namely foreign aid. The book attempts to answer questions such as: What are the driving factors of forced migration movements? How can refugee burdens be assessed and compared across different types of host countries? Who are the actors in international refugee protection and management, and how do they act? And finally, how does the phenomenon of international refugee movements, and specifically how do asylum seekers, influence the aid allocation politics of Western industrialized countries?
-- PART I: INTRODUCTION -- Research Objective -- Research Outline -- PART II: FORCED MIGRATION PATTERNS AND POLITICS -- Introduction -- Migration Characteristics -- Migration Types -- Migration Causes -- International Actors for Refugee Protection -- UNHCR and its Historical Background -- Other International Organizations -- National States -- Refugee Politics -- Burden-Sharing and International Cooperation -- Migration Prevention and Aid Assistance -- PART III: INTERNATIONAL REFUGEE BURDENS -- Introduction -- Assessing the Refugee Burden to Host Countries -- Methodology of a Refugee Burden Index -- Refugee Capacity Index -- Ability-to-care -- Socio-political Acceptance of Immigrants -- Politico-institutional Performance -- Refugee Gaps -- Refugee Burden Index -- Results -- Concluding Remarks -- PART IV: DETERMINANTS OF FORCED DISPLACEMENT -- Introduction -- Conflict History and Displacement in Aceh, Indonesia -- Theoretical Background of Displacements -- Empirical Analysis of Displacement in Aceh -- Data Source and Descriptive Statistics -- Empirical Strategy -- Estimation Models -- Main Control Variables -- Estimation Results -- Concluding Remarks -- PART V: THE POLITICAL ECONOMY OF REFUGEE MIGRATION -- Introduction -- Model Analysis -- The Cross-Border Option -- The Asylum-Seeking Option -- Counter-asylum Policies -- Defensive Asylum Policy: Asylum Restriction -- Decline in Self-Reliance in the Cross-the-Border Country -- Decline in Recognition Rates in the Western Asylum Country -- Proactive Asylum Policy: Migration Preventive Aid Transfers -- Aid to the First Asylum Country -- Aid to the Country of Origin -- Self-financing Proactive Asylum Policy -- Concluding Remarks -- PART VI: ASYLUM COOPERATION AMONG ASYMMETRIC COUNTRIES -- Introduction -- Literature Review -- The Analytical Framework -- Asylum Cooperation in the European Union -- Concluding Remarks -- PART VII: REFUGEE MOVEMENTS AND AID POLITICS -- Introduction -- Aid and Refugee Migration Policies -- Aid Allocation Patterns and Statistics -- UN Diplomacy and Aid Allocation -- Data -- Results -- Concluding Remarks t
Includes bibliographical references and index.
Keywords: Forced migration; Forced migration -- Political aspects; Forced migration -- Economic aspects